KH Mas'ud Al-Mudjenar's Spiritual Learning Model in the Pesantren Tradition - Ramadhan, Aditya; Albab, Hayyan Ahmad Ulul (Interdisciplinary Journal of Social Sciences, 2025)
Developing an Islamic boarding school requires thorough guidance and mentoring. One successful form of learning mentoring is through spiritual learning. This study employed a qualitative, descriptive approach. Data collection techniques included interviews, observation, and documentation. The analysis employed the theory of Milles and Huberman. The purpose of this study was to explore the biography of KH. Mais'ud Al-Mudjenair and the characteristics of KH. Mais'ud Al-Mudjenair's spiritual learning in developing the Darul Mustaighitsin Islamic Boarding School in Lamongan. The results of this study, first, are the biography of KH. Mais'ud Al-Mudjenair. Kyai Mais'ud Al-Mudjenair was born in Kediri on May 9, 1949. He studied at the Jampes and Lirboyo Islamic Boarding Schools, and served as a servant. He is the grandson of Mbah Kyai Kholifah Mudjenair. Kyai Mais'ud passed away on October 26, 2021. Second, the characteristics of KH. Mais'ud Al-Mudjenair's spiritual learning regarding religious values. The implementation of religious values can be carried out through several activities such as habituating the tadarus Al-Qur'an, tahlil, istighosah, manaqib, reciting the Al-Barzanji sholawat, and congregational prayer. Third, the characteristics of KH. Mais'ud Al-Mudjenair's spiritual learning regarding moral values. The implementation of moral values applied includes honesty, responsibility, and politeness. Fourth, the characteristics of KH. Mais'ud Al-Mudjenair's spiritual learning regarding the value of sincerity. The implementation of the value of sincerity applied is a form of devotion at the Darul Mustaighitsin Islamic Boarding School in Lamongan. Sincerity in carrying out duties solely because of the hope of Allah's pleasure. Fifth, the characteristics of KH. Mais'ud Al-Mudjenair's spiritual learning regarding the value of istiqomah. The implementation of the value of istiqomah applied is the istighosah activity every Monday night because this activity is the core of the Darul Mustaighitsin Islamic Boarding School. In essence, whatever the circumstances, istiqomah must be maintained.